Teksten voor de 21ste eeuw - Club van Antwerpen; Abicht, Ludo; Dethier, Hubert; Kruithof, Jaap; Lecompte, César; Mulier, Rita; Vandepitte, Marc (Berchem : EPO, 1988)
Schenking Karel Maes
Nederlands
Monografie